STUDI PIROLISIS MIKROALGA (Spirulina platensis) TERHADAP KONSENTRASI PRODUK TURUNAN KARBOHIDRAT - Qosim, Assyfa Machmudah; Subagyono, RR Dirgarini Julia Nurlianti; Gunawan, Rahmat (PROSIDING SEMINAR KIMIA, 2024)
Pyrolysis study of microalgae Spirulina platensis using Pyrolysis-Gas Chromatography-Mass Spectrometry (Py-GC/MS) instrument has been conducted. In the pyrolysis product of microalgae Spirulina platensis, the chemical composition of carbohydrate-derived products was 10.70%. The carbohydrate-derived product compounds produced were 2-methyl-propanal, phenol, and 1-hydroxy-2-propanone. Keywords: Spirulina platensis, pyrolysis, Py/GC-MS